Pejeriz: Rice, entrepreneurship and jobs in West Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2019)
The rice value chain in West Africa has huge potential to create new jobs for the region’s youth. Young people in the region offer an innovative and dynamic workforce, demonstrating a high uptake of modern technology and the ability to take on significant levels of risk. CTA’s Promoting youth entrepreneurship and job creation in the West African rice value chain (PEJERIZ) project is creating sustainable entrepreneurial and employment opportunities for rural youths by actively engaging them in the improvement of rice value chains.